Bola-bola Singkong dan Nugget Bayam sebagai Upaya Peningkatan Kreatifitas dan ekonomi ibu-ibu Dusun Bayeman, Sampung Ponorogo - Nasyiithoh, Hikma Khilda (Proceedings of Annual Conference on Community Engagement, 2018)
Cassava is one Cassava is one of the staple food ingredients of the Indonesian people, especially in the past era. In this day and age, the presence of cassava as a staple food is invincible with rice. One of the contributing factors is the mother’s habit of only introducing her child with rice as a staple food and a lack of variations in cassava processing. As a result, very few children today know and like cassava. In fact, cassava contains nutrients that are very beneficial for health and is a plant that is very easy to grow anywhere. Besides cassava, plants that are easily grown anywhere are spinach. Including in the hamlet of Bayeman, Kunti Village, Sampung District, Ponorogo Regency. Processed cassava in the hamlet is limited to steaming and chips. While processed spinach is only used for making clear vegetable ingredients. Community service groups with the Asset Based Community - Driven Development (ABCD) method try to provide training in making cassava balls and spinach nuggets in order to improve the creativity and economy of mothers around the Darul Hikmah Mosque in Bayeman Hamlet. The variety of processed cassava and spinach is expected to be able to make the reference of mothers in providing delicious processed foods that children like and also become a commodity of trade and new entrepreneurial fields for the residents of the village . Keywords :